2023
DOI: 10.1088/1361-6668/acdf8c
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in the low-field magnetization of Nb3Sn superconducting strands using the internal oxidation APC approach

Abstract: Nb3Sn superconductors are promising for building accelerator magnets for future energy-frontier circular colliders. A critical factor for this application is the low-field persistent-current magnetization because it leads to several critical issues: e.g., low-field instability (including flux jumps), hysteresis loss, and field errors in magnet bores. Suppression of low-field magnetization requires reduction of low-field critical current density (Jc) or effective subelement size (deff). However, reduction of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this report, we reanalyzed experimental data on the dependence of the maximum pinning force density, , from the average grain size, d , in practical low- T c multifilamentary Nb 3 Sn conductors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 55 , 56 , 58 ] fabricated by bronze and power-in-tube technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we reanalyzed experimental data on the dependence of the maximum pinning force density, , from the average grain size, d , in practical low- T c multifilamentary Nb 3 Sn conductors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 55 , 56 , 58 ] fabricated by bronze and power-in-tube technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive (over nearly five decades) R&D studies of Nb 3 Sn-based conductors have shown that the key factors affecting the in-field critical current in these wires are the local composition, structure, and morphology of the superconducting A-15 phase [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive (nearly five decades) R&D studies of Nb3Sn-based conductors have shown that the key factors affecting the in-field critical current in these wires are the local composition, structure, and morphology of the superconducting A-15 phase [9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%